Clinical consequences of a genetic predisposition toward higher benign prostate-specific antigen levelsResearch in context - Mingjian Shi; John P. Shelley; Kerry R. Schaffer; Jeffrey J. Tosoian; Minoo Bagheri; John S. Witte; Linda Kachuri; Jonathan D. Mosley (EBioMedicine, 2023)
Summary: Background: Prostate-specific antigen (PSA) levels are influenced by genetic variation unrelated to prostate cancer risk. Whether a genetic predisposition to a higher PSA level predisposes to a diagnostic work-up for prostate cancer is not known. Methods: Participants were 3110 men of African and European ancestries ages 45–70, without prostate cancer and with a baseline PSA < 4 ng/mL, undergoing routine clinical PSA screening. The exposure was a polygenic score (PGS) comprising 111 single nucleotide polymorphisms associated with PSA level, but not prostate cancer. We tested whether the PGS was associated with a: 1) PSA value > 4 ng/mL, 2) International Classification of Diseases (ICD) code for an elevated PSA, 3) encounter with a urologist, or 4) prostate biopsy. Multivariable Cox proportional hazards models were adjusted for age and genetic principal components. Analyses were stratified by age (45–59 years, and 60–70 years old). Association estimates are per standard deviation change in the PGS. Findings: The median age was 56.6 years, and 2118 (68%) participants were 45–59 years. The median (IQR) baseline PSA level was 1.0 (0.6–1.7) ng/mL. Among men ages 45–59, the PGS was associated with a PSA > 4 (hazard ratio [HR] = 1.35 [95% CI, 1.17–1.57], p = 4.5 × 10−5), an ICD code for elevated PSA (HR = 1.30 [1.12–1.52], p = 8.0 × 10−4), a urological evaluation (HR = 1.34 [1.14–1.57], p = 4.8 × 10−4), and undergoing a prostate biopsy (HR = 1.35 [1.11–1.64], p = 0.002). Among men ages 60–70, association effect sizes were smaller and not significant. Interpretation: A predisposition toward higher PSA levels was associated with clinical evaluations of an elevated PSA among men ages 45–59 years. Funding: National Institutes of Health (NIH).